A developed TaqMan probe-based qPCR was used to quantify the distribution of AMDV in various tissues of infected mink and its prevalence in northern China - Yang, Zaixing; Li, Yifan; Jiang, Yuxuan; Wu, Jingqi; Guan, Zhenhong; Ge, Junwei; Zhao, Lili (Frontiers in Veterinary Science, 2025)
Aleutian mink disease (mink plasmacytosis) is a severe immune complex-mediated condition caused by the Aleutian Mink Disease Virus (AMDV), the most significant pathogen affecting mink health in the industry. Several studies have shown that AMDV epidemics can result in millions to tens of millions of dollars in economic losses worldwide each year. In this study, we developed a TaqMan probe-based real-time PCR technology (TaqMan-qPCR) for the specific, sensitive, and reproducible detection and quantification of AMDV in mink tissues by the VP2 gene, achieving detection limits as low as 1.69 × 101 copies/uL of plasmid DNA and 8.50 × 10−3 ng/uL of viral DNA, and the established TaqMan-qPCR assay is 100 times more sensitive than PCR. Clinical samples of mink from different provinces showed a high prevalence of AMDV infection, 89.55% in Heilongjiang, 90.74% in Shandong, 80.23% in Hebei, 83.70% in Jilin, and 82.35% in Liaoning Province. Tissue distribution analysis showed that viral loads were generally high in all organs, especially in the mesenteric lymph nodes and spleen, and the virus was also detected in non-lymphoid tissues such as the brain, confirming the widespread distribution of AMDV throughout the body of mink. The established TaqMan-qPCR assay will become an important diagnostic tool for the prevention and control of AMDV, which is essential for disease management in mink populations.